Analysis of the psychometric properties of business studies achievement test for senior secondary schools in Nigeria - Ufondu, Chidiebere Christopher; Auta, Mohammed Adamu; Ifi, Chibuzor Christy (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2023)
The study analyzed the psychometric properties of business studies achievement test for senior secondary schools in Nigeria. One research question guided the study. The study adopted an instrumentation design. The area of the study was Anambra State. The population of the study consists of all 23,077 students and 586 business studies teachers in two hundred and sixty-one senior secondary schools in Anambra State. Taro Yamane formula was used to determine the sample size of the study, which is 630 made up of 393 students in SS1 and 238 business studies teachers in Anambra State. A multi-stage sampling procedure involving two stages was adopted for this study. Proportionate stratified and purposive sampling techniques were employed at the first and second stages respectively. Items were subjected to item analysis to determine the difficulty and discriminatory indices. The study revealed that 125 items were found to be appropriate for inclusion in the business studies achievement test, these test’s items met the criteria for item difficulty index and item discrimination. Based on the findings of the study it was recommended that teachers of business studies like commerce, accounting, and office practice among others should employ the created business studies Achievement Test. The BSAT items should be used as a model when creating other accomplishment exams for senior secondary schools in business studies.